2024
DOI: 10.1021/acsnano.3c07977
|View full text |Cite
|
Sign up to set email alerts
|

Multi-interface Combination of Bimetallic Selenide and V4C3Tx MXene for High-Rate and Ultrastable Sodium Storage Devices

Yilin Li,
Zeyu Yuan,
Dongdong Li
et al.

Abstract: Sodium-ion batteries (SIBs) have great potential as electrochemical energy storage systems; however, their commercial viability is limited by the lack of anode materials with fast charge/discharge rates and long lifetimes. These challenges were addressed by developing a multi-interface design strategy using FCSe (FeSe 2 / CoSe 2 ) nanoparticles on V 4 C 3 T x MXene nanosheets as conductive substrates. The heterogeneous interface created between the two materials provided high-speed transport of sodium ions, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Figure a illustrates the charge density distribution for CeO x @NiCo 2 O 4 , with cyan and yellow regions representing electron consumption and accumulation, respectively. It can be observed that the charge density tends to accumulate on the surface of CeO x at the interface between CeO x and NiCo 2 O 4 , indicating significant electron transfers from Co and Ni to CeO x This result further emphasizes the crucial role of hybrid structures in modulating electronic properties, thereby enhancing electrocatalytic performance. , The findings are consistent with the XPS results shown in Figure , which demonstrate positive shifts in the Co 2p and Ni 2p signals. Additionally, Figure b,c presents the densities of electronic states (DOS) for both CeO x @NiCo 2 O 4 and NiCo 2 O 4 .…”
Section: Resultssupporting
confidence: 85%
“…Figure a illustrates the charge density distribution for CeO x @NiCo 2 O 4 , with cyan and yellow regions representing electron consumption and accumulation, respectively. It can be observed that the charge density tends to accumulate on the surface of CeO x at the interface between CeO x and NiCo 2 O 4 , indicating significant electron transfers from Co and Ni to CeO x This result further emphasizes the crucial role of hybrid structures in modulating electronic properties, thereby enhancing electrocatalytic performance. , The findings are consistent with the XPS results shown in Figure , which demonstrate positive shifts in the Co 2p and Ni 2p signals. Additionally, Figure b,c presents the densities of electronic states (DOS) for both CeO x @NiCo 2 O 4 and NiCo 2 O 4 .…”
Section: Resultssupporting
confidence: 85%
“…1d ). 18 More importantly, compared with that in Cu 2 Se and MoSe 2 , the Cu-d band and Mo-d band in Cu 2 Se@MoSe 2 approached each other and sat closer to the Fermi energy, revealing that an electronic interaction between Cu-d to Mo-d. As displayed in the differential charge density images of Cu 2 Se@MoSe 2 ( Fig. 1e ), depletion of electrons at interfacial Cu atoms and accumulation of electrons at Mo atoms were observed.…”
Section: Resultsmentioning
confidence: 87%
“…15,16 Metallic selenides with various bandgaps can induce spontaneous electron redistribution at heterointerfaces to generate a built-in electric field (BiEF) that enhances ion transfer. 16–18 Analogically, designing a heterostructure involving MoSe 2 and another selenide could be promising to overcome aforementioned drawbacks, thereby achieving stabilized 1T-MoSe 2 and a BiEF for promoting the transfer of electrons and ions. Such a structure has not been reported for battery materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, its improvement in volume expansion and structural stability is limited and requires further exploration. 89,90…”
Section: Discussionmentioning
confidence: 99%